INVESTIGATION OF THE STRENGTH THRESHOLD OF RABBIT BLOOD VESSELS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article examines the biomechanical properties of rabbit blood vessels, taking into account the influence of climatic factors in the Republic of Uzbekistan. The aim of the study is to determine the strength threshold of the vascular wall and to analyze the effects of temperature, seasonal, and hydration conditions on its mechanical stability. The study employs experimental methods of mechanical testing of blood vessels, morphological analysis, and statistical data processing. The results obtained demonstrate that under hot climate conditions, changes in vascular elasticity are observed, including increased stiffness and a reduced strength threshold during dehydration of the organism. The practical significance of the study lies in the development of recommendations for the prevention of vascular complications under conditions of climatic stress.
Keywords: Blood vessels, strength threshold, biomechanics, climate, dehydration, elasticity.